A FLIPPED LEARNING ENVIRONMENT: A DISRUPTIVE APPROACH FOR TRADITIONAL CLASSROOMS? - Byabazaire Yusuf; Mohammed Ahmed Taiye (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The primary purpose of this study was to examine whether a flipped learning environment was a disruption to the traditional instructional approach, particularly in consideration of the 21st-century skills that students must acquire before graduation. A flipped classroom is one in which students are introduced to content at home or outside classroom via technology, and practice working through it at school. A qualitative research design was employed to conduct the study through a focus group approach. Nine in-service teachers, who were participants in a flipped classroom pilot program in Malaysia, served on the focus groups. Data were collected through asynchronous virtual focus group discussions. The scissor-and-sort approach was employed in the data analysis process. Findings from the study indicated teachers believed that a flipped learning environment maximized student learning potential, allowed for collaborative learning, created an engaging learning environment and promoted higher order critical thinking and problem solving skills, all suitable for encouraging and practicing 21st century skills in the classroom. Therefore, this study showed that the flipped classroom approach disrupts the traditional learning environment in a positive manner and avails opportunities to equip students with the relevant skills of problem-solving, critical thinking, collaboration, cultural sensitivity, and creativity which are essential for life-long learning and participating in a competitive 21st-century learning environment.